Spotlight on ORNAC Members: AN INTERVIEW WITH ESTHER ENG RN, BN, CPN(C) & ANNE CHANG RN, BN, CPN(C) WINNERS OF THE ORNAC PERIOPERATIVE NURSES WEEK CAMPAIGN CONTEST. - Harley, Catherine (Operating Room Nurses Association of Canada Journal, 2015)
Anne Chang graduated with a Bachelor’s of Nursing from the University of Calgary in 2004. She worked as a RN on a nephrology inpatient unit prior to being accepted in the Calgary Perioperative Nursing Program in 2005. She then spent the next 6 years working in the OR at the Peter Lougheed Centre in Calgary, AB, initially as a staff nurse and then as nurse clinician of General Surgery. In 2010 she received her CNA Certification in Perioperative Nursing. In 2011 she became the OR unit manager at Rockyview General Hospital (RGH) in Calgary, AB. In 2014 she made a career change and became a Clinical Safety Leader working with the Calgary Zone Patient Safety team within Alberta Health Services. Anne lives in Calgary with her husband and four children and during any spare time that remains she is committed to longdistance running. Esther Eng graduated with a Bachelor’s of Nursing from the University of Calgary in 2004. After graduation she worked casual on a surgical unit focusing on colorectal/gynaecological surgeries. She then worked part-time on a medical unit with a sub-acute neurological focus as well as working in long term care. She was accepted into the Calgary Perioperative Nursing Program in 2006 and worked at the Peter Lougheed Centre (PLC) Operating Room as a staff member gaining experience in all services. She completed her CNA Certification in Perioperative Nursing and eventually became unit manager of the PLC Recovery Room and then the PLC Operating Room/Minor Surgery Clinic. In 2014 she moved to the South Health Campus and took on a staff role in the Minor Surgery Clinic. She has a passion for OR Nursing and is currently the President of the South Central Operating Room Nursing Association (SCORNA). She lives in Calgary with her husband in Calgary and enjoys traveling, quilting, and scrapbooking.